The study of the thermal properties of gases in relation to physical theory, from Montgolfier to Regnault - Fox, R (1967)
One of the most important events in nineteenth-century physical science was the emergence, about the middle of the century, of a well founded and acceptable kinetic theory of gases. According to his theory gases were thought to be composed of particles which moved about rapidly with the walls of the containing vessel and so giving rise to the phenomenon of pressure. Since this is basically the view which we still accept today, it is not surprising that its origins and early development have provided a popular and profitable subject for historical research. Attempts to understand what it was that the kinetic theory replaced, on the other hand, have been far less numerous and all too often the earlier, erroneous opinions on gas structure have been dismissed in a brief introductory paragraph. We are told that before the advent of kinetic theory the particles of gases were thought to be stationary and that repulsive forces between them were postulated in order to account for pressure and for the characteristic property which all gases possess of expanding to fill completely any vessel in which they are placed. Such an account is essentially correct but it contributes little to our understanding of the true achievements of the early kineticists. It does not tell us, for example, whether the static theory which they rejected had developed over the years and attained some real degree of sophistication or whether it had never progressed beyond the status of a vague and arbitrary guess. Was it a fruitful theory which had been at the centre of scientific debate, throwing up important theoretical issues, or had it rather been an inhibiting factor? From one point of view the work which follows can be seen as an attempt to answer such questions as these by examining a research tradition to which the almost universal acceptance which was accorded the ‘static’ theory in the first half of the nineteenth century is obviously and specially relevant. Continued in thesis ...